The Relationship between Student Organizational Activity and Motivation to do Physical Activity - Muhammad Ali Hanif; Tatang Muhtar; Muhammad Nur Alif; Anggi Setia Lengkana (Journal of Physical Education Health and Sport, 2026)
Student involvement in campus organizations plays an important role in developing leadership, social skills, and academic experience; However, intensive organizational engagement may reduce students' attention to maintaining physical health. Limited physical activity among students has become a growing concern, particularly when organizational responsibilities compete with time for exercise. Based on this background, this study aims to examine the relationship between students' organizational involvement and their motivation for physical activity at the Universitas Pendidikan Indonesia, Sumedang Regional Campus. The study employed a quantitative approach with a correlational design. The population consisted of 592 students from six student organizations, and 247 respondents were selected through proportional random sampling using the Slovin formula. Data were collected using a Likert-scale questionnaire that has been tested for validity and reliability. Data analysis included descriptive statistics, normality testing, and Spearman's Rank correlation analysis due to non-normal data distribution. The findings revealed a significant relationship between organizational involvement and motivation for physical activity (Sig. = 0.001 < 0.05), with a correlation coefficient of 0.210, indicating a low level of correlation. The coefficient of determination (4.4%) shows that organizational involvement contributes only a small proportion to students' motivation for physical activity. In conclusion, although a statistically significant relationship exists, organizational involvement does not substantially influence exercise motivation. Therefore, integrating active lifestyle programs into student organizations is recommended to support holistic student development.